2020
DOI: 10.1101/2020.01.30.927210
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Common default mode network dysfunction across psychopathologies: A neuroimaging meta-analysis of the n-back working memory paradigm

Abstract: 41The National Institute of Mental Health's (NIMH) Research Domain Criteria (RDoC) classifies 42 disorders based on shared aspects of behavioral and neurobiological dysfunction. One common 43 behavioral deficit observed in various psychopathologies, namely ADHD, addiction, bipolar 44 disorder, depression, and schizophrenia, is a deficit in working memory performance. However, 45 it is not known to what extent, if any, these disorders share common neurobiological 46abnormalities that contribute to decrements in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 151 publications
(55 reference statements)
4
10
0
Order By: Relevance
“…The features used by the best EN-Back models suggest that as ADHD symptomatology increases, activation in task positive regions (DLPFC, PPC, and caudal ACC) decreases and activation in task negative regions (VMPFC, posterior cingulate cortex, lateral temporal cortex, precentral, and postcentral gyri) increases. This is highly consistent with the existing literature, which has shown that during working memory tasks, individuals with ADHD show reduced activation in task positive regions 8,38,39 and increased activation in task negative regions 40 . The CSA features identified by the best sMRI model overlapped considerably with those in the EN-Back models; ADHD symptomatology was predicted by less CSA in the DLPFC, caudal ACC, and lateral temporal cortex.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The features used by the best EN-Back models suggest that as ADHD symptomatology increases, activation in task positive regions (DLPFC, PPC, and caudal ACC) decreases and activation in task negative regions (VMPFC, posterior cingulate cortex, lateral temporal cortex, precentral, and postcentral gyri) increases. This is highly consistent with the existing literature, which has shown that during working memory tasks, individuals with ADHD show reduced activation in task positive regions 8,38,39 and increased activation in task negative regions 40 . The CSA features identified by the best sMRI model overlapped considerably with those in the EN-Back models; ADHD symptomatology was predicted by less CSA in the DLPFC, caudal ACC, and lateral temporal cortex.…”
Section: Discussionsupporting
confidence: 92%
“…Even without accounting for sociodemographic factors, the best models for SST and MID were not effective at predicting ADHD symptomatology. Based on literature demonstrating individuals with ADHD symptomatology show poorer performance and different neural activation for working memory 38 , inhibitory control 9,11 , and reward processing 10 , we were surprised to see only working memory activation was able to predict ADHD symptomatology.…”
Section: Discussionmentioning
confidence: 93%
“…The features used by the best EN-Back models suggest that as ADHD symptomatology increases, activation in task positive regions (DLPFC, PPC, caudal ACC) decreases and activation in task negative regions (VMPFC, posterior cingulate cortex, lateral temporal cortex, precentral and postcentral gyri) increases. This is highly consistent with the existing literature, which has shown that during working memory tasks, individuals with ADHD show reduced activation in task positive regions 8,38,39 and increased activation in task negative regions 40 .…”
Section: Discussionsupporting
confidence: 92%
“…Even without accounting for sociodemographic factors, the best models for SST and MID were not effective at predicting ADHD symptomatology. Based on literature demonstrating individuals with ADHD symptomatology show poorer performance and different neural activation for working memory 38 , inhibitory control 9,11 , and reward processing 10 , we were surprised to see only working memory activation was able to predict ADHD symptomatology.…”
Section: Discussionmentioning
confidence: 92%
“…Research has shown that people show better executive function capacities when they feel happy, socially supported, and healthy (53). Conversely, de cits in executive function have been associated with depression, and various psychopathologies (54). Our ndings suggest that in this population of Guatemalan adults executive function had little if any association with psychological wellbeing and mental health constructs.…”
Section: Discussionmentioning
confidence: 55%